2005
DOI: 10.1158/0008-5472.can-04-3953
|View full text |Cite
|
Sign up to set email alerts
|

A Cell Proliferation Signature Is a Marker of Extremely Poor Outcome in a Subpopulation of Breast Cancer Patients

Abstract: Breast cancer comprises a group of distinct subtypes that despite having similar histologic appearances, have very different metastatic potentials. Being able to identify the biological driving force, even for a subset of patients, is crucially important given the large population of women diagnosed with breast cancer. Here, we show that within a subset of patients characterized by relatively high estrogen receptor expression for their age, the occurrence of metastases is strongly predicted by a homogeneous ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
186
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(212 citation statements)
references
References 32 publications
24
186
0
2
Order By: Relevance
“…Remarkably, gene expression profiling has also identified recently an up-regulation of cell cycle and cell proliferation relevant genes in a distinct poor prognosis subgroup of patients in this tumor entity (31). In particular, there is a considerable overlap in genes or gene families (CCNB2, CDC45L, MAD2L1, KIF23, PTTG2, ORC6L, and KNSL6) identified between the current and the breast cancer study (31). Moreover, similar results have been obtained recently for aggressive neuroblastoma (32) and poor prognosis lung squamous cell carcinoma (33).…”
Section: Discussionmentioning
confidence: 97%
“…Remarkably, gene expression profiling has also identified recently an up-regulation of cell cycle and cell proliferation relevant genes in a distinct poor prognosis subgroup of patients in this tumor entity (31). In particular, there is a considerable overlap in genes or gene families (CCNB2, CDC45L, MAD2L1, KIF23, PTTG2, ORC6L, and KNSL6) identified between the current and the breast cancer study (31). Moreover, similar results have been obtained recently for aggressive neuroblastoma (32) and poor prognosis lung squamous cell carcinoma (33).…”
Section: Discussionmentioning
confidence: 97%
“…BUB1B is required for metaphase arrest in response to a lack of bipolar attachment. Overexpression of this protein is associated with a decrease in chromosomal stability and poor outcome in breast cancer patients (Warren et al, 2002;Dai et al, 2005). CDC20 is necessary for the degradation of an S-phase cyclin, which can antagonize APC activity (Harper 25 et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…3 In brief, this was accomplished by the use of a biotinylated hydrazide instead of a solid-phase hydrazide to label only the cell surface glycoproteins on live B and T lymphocytes in culture. After labeling, total membrane proteins were again isolated from the cells (14) and were then proteolyzed with trypsin.…”
Section: Methodsmentioning
confidence: 99%
“…Although gene expression array studies on cells and tissues have shown that such markers, or marker panels, do exist and can be associated with pathological changes in the disease and its prognoses (2,3), most tissues are not readily accessible for routine gene expression screening, and the affected tissue segments might be difficult to identify a priori.…”
mentioning
confidence: 99%